An overview on the use of hemp (Cannabis sativa L.) in animal nutrition - Klir, Željka (Array, 2019)
The aim of the paper was to research the possibility of using hemp (Cannabis sativa L.) in animal nutrition. In animal nutrition, hemp seeds can be used, as well as hempseed cake, and hemp oil as supplement in feed mixtures. Hemp seeds are rich in crude protein and crude fat with adequate proportions of linoleic (LA, C18:2 n-6) and linolenic (ALA, C18:3 n-3) acid. The addition of hemp oil in diets of dairy goats increased milk fat with increasing conjugated fatty acid (CLA) and polyunsaturated fatty acids (PUFA) proportions. When feeding ewes with addition of hemp seeds (180 g/day) or hempseed cake (480 g/day), higher milk fat content was observed with higher proportions of LA, CLA and ALA. Addition of hempseed cake (143 g/ kg DM) in diets of cows increased milk yield, compared to the control group and the group with higher levels of hempseed cake (233 or 318 g/kg DM). Nutrition of laying hens with hemp seeds in diet (10 and 20%) provided enrichment of yolk fat with ALA, and did not negatively influence laying performance. The aforementioned indicated possibility of using hemp in diets of animals without major changes in production, and with possible increase of desirable fatty acids in animal products.